L. V. Pustovalov and the establishment of sedimentary research in Russia - V. G. Kuznetsov (Известия высших учебных заведений: Геология и разведка, 2023)
This article is dedicated to the role of L.V. Pustovalov in creating the theoretical foundations of sedimentary research in Russia, including determination and substantiation of the most important regularities governing sedimentary processes and their stages. The constituting stages of sedimentary processes, such as weathering, transport, and deposition, were identified and described. These stages lead to the differentiation of sedimentary material and the formation of sedimentary rocks of different composition and structure. The concepts of the stages of diagenesis and epigenesist (catagenesis) were formulated. For the first time, specific features of sedimentary process evolution were outlined, including sedimentation conditions and formation of individual sedimentary minerals and rocks.